Analysing Discrimination based on Genetic Information - Akash, Akash; Sarker, Shuvro Prosun (University of Jember, 2024)
This paper analyzes and critiques existing literature on discrimination based on genetic information collected during genetic tests of individuals and the legal issues attached therewith. Genetic variations, which can lower or raise disease risk, result from the inheritance of parental genes. Subjecting individuals to stigmatization based on their unique ancestry or genetic status raises legitimate concerns. The literature review reveals that the issue of discrimination based on genetic information has occurred in countries like the United States and Canada. Accordingly, concerns regarding new forms of discrimination arising from the collection of information during genetic testing have grown over the decades in the wake of technological advancements in biotechnology, health, and allied sciences, as several studies have revealed. On the contrary, more material sufficiency in India necessitates consulting data from various disciplines. A conceptual framework is proposed to examine the theoretical foundations of non-discrimination provisions, compare genetic information non-discrimination legislation in the United States and Canada to India, and evaluate the practicality of implementing such laws in India. The initial testing of this framework suggests that due to insufficient legislation, there may be a need for enforceable measures to mitigate genetic information-related discrimination in India. The research problem requires qualitative research to gain an in-depth comprehension of experiences, phenomena, and context. This paper makes two main contributions: establishing a comprehensive background to allow comparisons by scholars and policymakers on the matter and helping to further the debate on the subject to generate value-based research regarding the ethical, legal, and social impacts of genetic research and anti-discrimination laws.KEYWORDS: Non-discrimination, Genetics and law, Literature review, Genetic discrimination.